Implementasi Kebijakan Pendidikan Islam di Era New Normal Terhadap Pembentukan Akhlak Peserta Didik - Nadhiroh, Ulfatun Naili (Al-Fikri: Jurnal Studi dan Penelitian Pendidikan Islam, 2021)
The Covid-19 pandemic is a real threat to anyone, including the world of Islamic education in Indonesia. Education policies that have been comfortable so far have had to undergo a significant overhaul. Issuance of the Decree of the Director General of Education Number 2791 of 2020 regarding emergency curriculum guidelines for madrasas to be used as a reference during learning activities in the midst of the Covid-19 pandemic until the implementation of the new normal. Learning activities using online also enliven the world of Islamic education. Various online media are used, including: Whatsapp, Zoom, Google Meet, Youtube, and so on. This paper wants to examine more deeply related to the implementation of Islamic education policies in the new normal era in relation to the moral formation of students. Although the implementation of online learning activities through android and web applications can foster student interest and motivation to learn, the problems of the policy cannot be avoided. This study uses Library Research with descriptive analysis related to literature, both from journals, books, and online news. There are several results, that learning policies using online media have a major impact on individual self-change, namely students become addicted so that it affects their morals. So the importance of the role and function of teachers and parents in providing guidance, so that the morals of students are more focused and the goals of Islamic education can be achieved.